دور استخدام نظم دعم القرار في تحسين الميزة التنافسيَّة "دراسة ميدانيَّة على الجامعات الخاصَّة العاملة في السَّاحل السُّوري" - اسبر, سعيد; غريب, محمد كمال عامر (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This research was conducted to determine the effect of the use of decision support systems on improving the five-dimensional competitive advantage (quality, cost, Flexibility, speed and creativity) in a sample of private universities operating in the Syrian coast. The researcher distributed (110) questionnaires to managers and employees in the universities under study. The number of recovered and valid questionnaires which were discharged was (92). The researcher analyzed the data using the Statistical Analysis Program (SPSS 25). At the end of this research, the researcher reached a number of conclusions, the most important of which is: There is a significant effect on the use of decision support systems to improve the five dimensions of competitive advantage in the universities under study. The researcher also made a number of recommendations, including: The need to interest in training managers and employees and decision makers in the use of decision support systems and increase their knowledge in the areas of computer use and related programs, and the management of the universities under study should: work on continuous improvement of the type of technology used, facilities, equipment, equipment and technical and administrative equipment of these universities, and the need to work on the development of special strategies aimed at improving the quality of services provided by the universities under study and evaluated continuously. هدف هذا البحث إلى تحديد مدى تأثير استخدام نظم دعم القرار في تحسين الميزة التنافسيَّة بأبعادها الخمسة (الجودة، التَّكلفة، المرونة، السُّرعة والإبداع)، وذلك في عيِّنة من الجامعات الخاصَّة العاملة في السَّاحل السُّوري. قام الباحث بتوزيع (110) استبياناً على المديرين والعاملين في الجامعات محلِّ الدِّراسة، وقد بلغ عدد الاستبانات المستردَّة والصَّالحة للتَّحليل والَّتي تمَّ تفريغها (92) استبانة. قام الباحث بتحليل البيانات باستخدام برنامج التَّحليل الإحصائي (SPSS 25). وفي نهاية هذا البحث توصَّل الباحث إلى مجموعة من الاستنتاجات وأهمّها: يوجد تأثير معنوي لاستخدام نظم دعم القرار على تحسين الأبعاد الخمسة للميزة التنافسيَّة في الجامعات محلِّ الدِّراسة. كما تقدَّم الباحث في نهاية البحث بمجموعة من التَّوصيات والَّتي كان أهمُّها: ضرورة الاهتمام بتدريب المديرين والعاملين ومتَّخذي القرارات في الجامعات محلِّ الدِّراسة على استخدام نظم دعم القرار وزيادة معارفهم بمجالات استخدام الحاسوب والبرامج ذات العلاقة، العمل على التَّحسين المستمر لنمط التِّقانة المستخدم والمرافق والتَّجهيزات والأدوات والمعدَّات التِّقنية والإداريَّة الخاصَّة بهذه الجامعات، وضرورة العمل على وضع استراتيجيات خاصة تهدف إلى تحسين جودة الخدمات المقدَّمة من الجامعات محلِّ الدِّراسة وتقييمها بشكل مستمر.